Pengaruh Electronic Word of Mouth terhadap Niat Beli Smartphone Merek iPhone yang di Mediasi Oleh Citra Merek: Studi pada Mahasiswa Manajemen Universitas Negeri Makassar - Nurul Afiah Almunawarah; Siti Hasbiah; Ilma Wulansari Hasdiansa; Isma Azis Riu; Nurul Fadilah Aswar (JURNAL RISET MANAJEMEN (JURMA), 2026)
This study aims to analyze the influence of electronic word of mouth (E-WOM) on purchase intention of iPhone brand smartphone through brand image as a mediating variable in Management students of Makassar State University. This study is motivated by the rapid development of digital technology and the increasing use of social media as a source of information that influences consumer perceptions and purchasing decisions, especially among students. The phenomenon of the rise of online product reviews, comments, and recommendations makes E-WOM an important factor in shaping brand image and driving consumer purchase intention. This study uses a quantitative explanatory approach survey method with purposive sampling technique, then analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the help of SmartPLS. The results show that electronic word of mouth (E-WOM) has a positive and significant effect on purchase intention and brand image, brand image also has a positive and significant effect on purchase intention, and is able to significantly mediate the relationship between E-WOM and purchase intention of iPhone brand smartphone. These findings indicate that the better the quality of information and reviews conveyed through E-WOM, the stronger the brand image formed and the higher the consumer's purchase intention.